PROCALCITONIN FOR IMPROVED ASSESSMENT AND AN ANSWER TO SEPSIS DILEMMA IN CRITICALLY ILL - A MYTH, A HYPE, OR A REALITY ? - Sharma, Raghava; Vijayakumar, Maniyar (Journal of Health and Allied Sciences NU, 2014)
Background and objectives: “Sepsis is a major cause for mortality in critically ill patients all over the world. The number of patients presenting with sepsis, septic shock is gradually increasing in daily clinical practice. Mortality in sepsis is mainly due to a delay in diagnosis and initiation of specific therapy(antibiotics).This is in turn mainly attributed to the difficulty in differentiating infectious trigger(sepsis) from non infectious triggers as both present with similar clinical features. Lack of specific marker adds to this dilemma of differentiating infectious and non infectious factors in critically ill patients.Recently there are some reports from European countries on role of Procalcitonin (PCT) in critically ill patients. Draw backs of these studies are galore mainly due to the difficulties in interpretation of results, as varying definitions for sepsis are used. But also there is paucity of data on Procalcitonin from Indian sub continent. Hence in the present single centre prospective observational study conducted at tertiary care medical college hospital , A total of 50 adult patients with sepsis fulfilling ACCP/SCCM guidelines were included, out of which 23 were in SIRS/Sepsis, 14 in severe sepsis and 13 in septic shock. Procalcitonin was evaluated in the first 24 hours after admission and before initiation of any antibiotic therapy. The role of procalcitonin was analyzed in relation to confirming sepsis, assessing the severity of sepsis and assessing the prognosis(possible out come) of sepsis. Combined role of procalcitonin with other indicators especially ESR, SOFA Score, Blood/relevant material culture was explored.Results: Our study confirmed the importance of procalcitonin in critically ill patients particularly in improving the predictive power while solving the sepsis dilemma.Conclusions: From our study, we conclude that Procalcitonin is not a myth nor a hype but it is a hard reality and is an answer to sepsis dilemma. It is therefore preferable to add Procalcitonin into the standard workup of critically ill patients with suspected sepsis in every day clinical practice.
Keywords: Procalcitonin; PCT; SOFA Score; Sepsis; Septic shock; ACCP/SCCM guidelines; Sepsis dilemma